Endowment Effects and Drinking Water Quality. (30th August 2016) - Booth, Pamela L.; Guilfoos, Todd; Uchida, Emi
Abstract : We conduct a laboratory experiment to test for the existence of the endowment effect—a gap between willingness to accept and willingness to pay—for improved drinking water quality using a within-subject design. We find a statistically significant and positive gap. Willingness to accept is 62 to 125 cents higher than willingness to pay on average, indicating the presence of endowment effects. This gap is robust to information about the quality of water being consumed. We also identify some heterogeneity in the size of the gaps that is associated with differences in subjects' knowledge of drinking water quality and disparities in their incomes.